Evaluating food sanitation, hygiene, and quality in the nutrition installation of an Indonesian mental hospital: A qualitative study - Yuniar, Nani; Effendy, Devi Savitri; Bahar, Hartati; Syamsuddin, Syam Sinar (YCAB Publisher & IAKMI SULTRA, 2023)
Background: Food sanitation and hygiene is an effort to control factors such as the environment, equipment, personnel, and food items that may cause health problems, diseases, or food poisoning. Hospitals are healthcare institutions that provide comprehensive individual healthcare. One crucial aspect of healthcare services in hospitals is nutrition installation, which plays a vital role in the patients' recovery process. Objective: This study aimed to analyze the food sanitation, hygiene, and quality at the Nutrition Installation of the Southeast Sulawesi Provincial Mental Hospital in 2022. Methods: This study employed qualitative research with a phenomenological approach. The information was sourced from two key informants and four ordinary informants. Data collection methods included in-depth interviews to explore the topic thoroughly, careful and direct observations, documentation through photographs of relevant phenomena, symbols, and signs, as well as recording dialogues during the research process. Triangulation techniques, including source, method, and research time, were used to ensure data and information validity. Data analysis involved classification, sorting, and presentation. Results: The findings indicated that the food storage and processing practices complied with the requirements outlined in Decree of Indonesia Minister of Health (Permenkes) No. 1096 of 2011. However, the selection of foodstuffs, food presentation, food transportation, and personal hygiene of food handlers do not meet the standards. Furthermore, based on the assessment of the physical feasibility of food sanitation hygiene at the nutrition Installation of the hospitals, a score of 80 was obtained, which falls below the minimum requirement specified in the requirement. Conclusion: The study revealed a significant non-compliance with the use of personal protective equipment (PPE) by food handlers during food processing and serving. Furthermore, health checks were not conducted, and the Nutrition Installation of the selected hospitals lacked a certificate of sanitary hygiene eligibility.